Renewable and Non-Renewable Energy Consumption and Economic Growth in Africa: Regional Insights for Sustainable Energy Planning - Aromasodun, Ololade; Biala, Musa; Shitu, Abdul (International Journal of Sustainable Energy Planning and Management, 2025)
Effective long-term planning becomes essential as Africa strives to expedite its shift to sustainable energy systems and comprehends how energy consumption and economic growth interact. This study examines the effects of total energy consumption, renewable energy consumption, and non-renewable energy consumption on economic growth in eight regional economic communities in Africa—AMU, CEN-SAD, COMESA, EAC, ECCAS, ECOWAS, IGAD, and SADC—between 1996 and 2022. Using panel data from the African regions, the Mean Group and Pooled Mean Group were utilised where applicable as indicated by the Hausman Test. The findings reveal that while both renewable and non-renewable energy consumption influence economic growth, their impacts vary across regions. Total energy consumption has a negative impact on economic growth in AMU, CEN-SAD, COMESA, ECCAS, and SADC blocs, but a positive impact on economic growth in ECOWAS and IGAD blocs, and an insignificant impact on the EAC bloc. While non-renewable energy consumption has a negative impact on economic growth in the AMU, COMESA, ECCAS, IGAD, and SADC blocs and a positive impact on economic growth in the EAC bloc, renewable energy consumption has a positive impact on economic growth in the AMU, COMESA, ECCAS, IGAD, and SADC blocs. These findings highlight the necessity of unique, region-specific energy planning approaches that give system resilience and investments in renewable energy top priority. Specifically, policymakers should expand energy access to underserved areas for the blocs experiencing positive impact of energy consumption, while those blocs experiencing negative impact should put in place policies to reduce energy waste and control energy prices to avoid volatility.